Devisa dan Turis Mancanegara - Teguh Permana; Andriani Puspitaningsih (EDUTOURISM Journal Of Tourism Research, 2020)
This study aims to determine the economic conditions in terms of foreign tourists as foreign exchange earners during the Covid19 pandemic in Indonesia. The research method used is descriptive method and content analysis. Broadly speaking, the systematic writing is more narrative that collects the opinions of experts, journals, books and writings published on the internet related to foreign exchange and foreign tourists. The results showed that foreign exchange and foreign tourists experienced a very large decline since the spread of the Covid19 virus. The research findings imply that the government must immediately take quick steps to overcome this in order to increase the country's foreign exchange.